Urbanity - Gabriel Ahlfeldt (Center for Economic Studies and ifo Institute (CESifo), 2013)
I define a composite amenity that provides aesthetic and consumption value to local residents: Urbanity. A novel data set of geo-tagged photos shared in internet communities serves as a proxy for urbanity. From the spatial pattern of house prices and photos I identify the value of urbanity in two of the largest European cities, Berlin and London. I find an elasticity of indirect utility with respect to urbanity of about 1%. The aggregated willingness to pay equates to about 1 bn per year in each city or, on average, 1.5% of household income. The results demonstrate the important role cities paly as centers of leisure, consumption and beauty.
Keywords: R20; R30; 330; amenities; consumer city; hedonic analysis; photography geography; property prices